Method Development for Drugs and New Psychoactive Substance Analysis in Blood by Liquid Chromatography - Tandem Mass Spectrometry (LC-MS/MS) - ยกเชื้อ, ธนสิริ (YRU Journal of Science and Technology, 2018)
Forensic toxicology is involved with the detection and identification of drugs and poisons in biological samples such as blood to assist in death investigations and in drug of abuse testing in the living for example in the case of sexual assaults. In recent years, the use of new type of narcotic substances which is known as “New psychoactive substances” or NPS has been increasing globally and the detection methods for NPS in blood are not widely known in Thailand. Furthermore, the very low level of drug concentration in blood at therapeutic level (nanogram or sub-nanogram level) is a main problem for drug identification in blood sample. LC-MS/MS (Tandem Mass spectrometry) which is considered as a highly sensitive technique is required to solve this problem. This article presents the method development for drug and NPS analysis in blood by LC-Triple-Quadrupole with dynamic multiple reaction monitoring (dMRM) mode. Results showed that LC/MS/MS method that was developed can identify 34 drugs and NPS in blood at therapeutic level with the limit of detection of 0.5 ng/ml.